Hot models. (Economist, 2005)
This article looks at methods used to research the impact of climate change on environmental health. This month saw the start of a period when climate change will be in the news a lot. On February 16th the Kyoto protocol comes into force. As part of the fun, there was also the publication of an intriguing paper in Nature. The research was intriguing not so much for what it said (things may get hotter than expected), but for how it arrived at that conclusion. For it was one of the first serious scientific studies to exploit the idea of distributed computing. Modelling the climate requires a huge amount of computing power, which is one reason the models have not been tested as thoroughly as they might have been. So David Stainforth of Oxford University and his colleagues decided to employ the idle capacity of 95,000 private desk-top computers to do it for very little money. Its description of the interaction between atmosphere and ocean is far too simple. But it does point the way towards a better way of doing the modelling business. And a cheaper one, too.